KORELASI KETERAMPILAN MEMBACA PEMAHAMAN DENGAN KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 25 PADANG - Zikri, Hasnuz; Hafrison, Mhd. (Universitas Negeri Padang, 2020)
ABSTRACTThe purpose of this study is three. First, it describes the writing skills of the description text of grade VII students of SMP Negeri 25 Padang. Second, describe the reading comprehension skills of the VII grade students of SMP Negeri 25 Padang. Third, analyze the correlation between reading comprehension and description text skills with the writing skills of the VII grade students of SMP Negeri 25 Padang. This type of research is quantitative research with descriptive methods. The design (design) in this study is correlational. By using simple random sampling technique, the sample in this study amounted to 48 students. The research instrument was an objective test to measure comprehension reading skills and performance tests to measure description writing skills. The conclusion of this research is thirteen. First, the description writing skills of grade VII students of SMP Negeri 25 Padang are in good qualifications. Second, reading comprehension text skills of the seventh grade students of SMP Negeri 25 Padang are in good qualifications. Third, there is a significant relationship between reading comprehension text description skills and writing text description of students in grade VII of SMP Negeri 25 Padang at n-1 degrees of freedom and a significant level of 95%. H0 is rejected and H1 is accepted because the test results prove that the value is greater than t table (2,468> 1.68). Kata Kunci : Korelasi, Kemampuan Membaca Pemahaman, Keterampilan Menulis Teks Deskripsi